Effect of Personal Characteristics of Respondents on their Perception towards Over-exploitation of Water Resources - Shubham; Rati Mukteshawar, Anil Kumar Rohila, Joginder Singh Malik, Amit Kumar, Rohtash Kumar (Indian Journal of Extension Education, 2022)
The study was carried out in the purposively selected five districts of Haryana state due to intensive agricultural practices followed in these districts. Mainly rice-wheat cropping pattern was followed in selected districts along with sugarcane and maize. The objective of this study was to know the relationship of the personal characteristics of respondents with the perception of the over-exploitation of water resources. The data were collected from 150 respondents comprising 15 respondents from randomly selected ten villages through a well-prepared interview schedule. Age, education, land holding, mass media exposure, and extension contact were significantly correlated with the perception of respondents. Age was negatively correlated while, education, land holding, mass media exposure, and extension contact were positively correlated with the perception of respondents and the independent variables in the regression equation jointly explained the variation of 22.70 percent. There is a need to organize awareness campaigns and training to develop a favorable perception of the over-exploitation of water resources.